Legal nature of the proceedingsand the decision to grant a scholarship forthe phdcandidate in Polish law - Majewski, Kamil (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
Polish Law on Higher Education , as a legal act shall apply to public and non-public higher education institutions (Article 1 (1) of the LoHE), also regulates issues related to the PhD candidate’s situation, including the form of financial support for PhD candidates. According to Article 199 (1) of the LoHE, PhD candidate may receive financial support of the following types: 1. Maintenance grant; 2. Assistance grant; 3. Scholarship for outstanding PhD candidates; 4. Special grant for disabled persons; 5. Scholarship for outstanding achievement awarded by the minister.